President's Annual Report, 1951-1952 - Thaxton, J. Ralph, Dr. (Valdosta State University Archives and Special Collections, 1952)
The annual report to the Chancellor of the University System of Georgia for 1951-1952. Summarizes activity in faculty hiring, firing, and resignations. Also mentions faculty that are taking graduate coursework. Describes assembly programs. Provides information on average faculty pay for full Professors, Associate Professors, Assistant Professors, and Instructors. Tables provide information such as faculty teaching loads, student courseloads, enrollment, degrees conferred, and enrollment by county. Additional tables include data on student scholarship, student exclusions, probations, and Dean's List. Activities in the Dean of Women's Office and the Publicity Office are discussed, including preparations for male dormitories. Extracurricular activities for the year, including sports, are summarized. New curricula and library activity are mentioned, along with an appended Report of the Librarian, which discusses expenditures, projects and circulation. New constructions and gifts to the university are discussed.
Keywords: Valdosta State University; College publications; Corporate reports; College presidents